2017
DOI: 10.5527/wjn.v6.i4.176
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between hypoalbuminemia and acute kidney injury

Abstract: Our meta-analysis published in 2010 provided evidence that low levels of serum albumin (hypoalbuminemia) are a significant independent predictor of acute kidney injury (AKI) and death following AKI. Since then, a large volume of additional data from observational clinical studies has been published further evaluating the relationship between serum albumin and AKI occurrence. This is an updated review of the literature to re-evaluate the hypothesis that hypoalbuminemia is independently associated with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 70 publications
4
58
2
3
Order By: Relevance
“…Cumulative evidence have shown that hypoalbuminemia is an important risk factor for postoperative AKI in various clinical settings [8][9][10][11][12]. However, in surgical settings, studies were mainly focused on cardiac surgery and transplant surgery [11,12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative evidence have shown that hypoalbuminemia is an important risk factor for postoperative AKI in various clinical settings [8][9][10][11][12]. However, in surgical settings, studies were mainly focused on cardiac surgery and transplant surgery [11,12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is a well-established risk factor for increased morbidity and mortality in acutely ill patients [7]. The association between hypoalbuminemia and AKI is consistently evident in many observational studies conducted across different clinical settings, mainly focusing on infectious diseases, cancer, cardiac surgery, and transplant surgery [8][9][10][11][12]. Although the underlying mechanisms for this association are not fully elucidated, serum albumin may play a protection role in the maintenance of renal perfusion, preservation of proximal tubular integrity and function, binding of endogenous toxins and nephrotoxic drugs, prevention of oxidative damage, and delivery of protective lysophosphatidic acid [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative evidence have shown that hypoalbuminemia is an important risk factor for postoperative AKI in various clinical settings [8][9][10][11][12]. However, in surgical settings, researches were mainly focused on cardiac surgery and transplant surgery [11,12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is a well-established risk factor for increased morbidity and mortality in acute illed patients [7]. The association between hypoalbuminemia and AKI is consistently evident in a wealth of observational studies conducted across different clinical settings, mainly focusing on infectious diseases, cancer, cardiac surgery and transplant surgery [8][9][10][11][12]. Although the underlying mechanisms for this association are not fully elucidated, serum albumin may play a protection role in maintenance of renal perfusion, preservation of proximal tubular integrity and function, binding of endogenous toxins and nephrotoxic drugs, prevention of oxidative damage and delivery of protective lysophosphatidic acid [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Açık kalp cerrahisi planlanan bazı hastalarda preoperatif dönemde veya postoperatif dönemde kardiyopulmoner baypasa bağlı olarak albümin düşüklüğü görülebilir. Hipoalbüminemi akut böbrek hasarı için bir ön belirteç olarak kabul edilmektedir [8,9] . Postoperatif dönemde hipoalbüminemi ile ABH birlikteliği artmış morbidite ve mortalite ile ilişkilidir [10] .…”
Section: Introductionunclassified